SOSIALISASI DAN PENERAPAN PENGGUNAAN PUPUK ORGANIK PADA TANAMAN HORTIKULTURA (Studi Kasus KWT Bunda Ceria) - Yulida, Roza; Adelia Herni, Virna; Arya Fachrizal, M.; Asrizal, Meki; Arif; Saputri, Wahdini; Arystia, Richa; Maulana Hanif, Ariel; Handoko, Ricky; Al-Fath, Zikra; Jannah Khairin, Miftahul (JP2N : Jurnal Pengembangan Dan Pengabdian Nusantara, 2025)
Household food security is a crucial issue directly related to community well-being and environmental sustainability. The high dependence of smallholder farmers on chemical fertilizers has the potential to cause soil degradation and exacerbate environmental pollution. Therefore, efforts are needed to introduce environmentally friendly agricultural systems through the use of organic fertilizers. This community service activity aims to improve the understanding and skills of members of the Bunda Ceria Women Farmers Group (KWT) in RW 02, Sialangrampai Village, Kulim District, Pekanbaru City, in applying organic fertilizers to horticultural crops, particularly chilies and eggplants. The target group is the women members of the KWT who play an important role in supporting family food security. The method used is civic engagement through the stages of problem identification, outreach, technical training, field implementation, and direct field assistance. The commodities planted include chilies and eggplants, which have high economic value and are in accordance with local needs. The results of the activity show an increase in the ability of KWT members to utilize yard land productively, the application of organic fertilizers as an alternative to chemical fertilizers, and the formation of a more environmentally friendly household farming system. Furthermore, this activity encourages the development of a culture of mutual cooperation, increased knowledge, and opportunities for additional family income from harvests. Thus, this program contributes to supporting food security, empowering women, and strengthening the local economy based on sustainable agriculture.